Cherchez l'Electron. Issue 2 (8th September 2017) - Mäser, Pascal
Summary: Who wouldn't want to have a drug that is activated only in the target cell? Prodrugs that are metabolically triggered inside the pathogen but not in the host are an attractive concept in antimicrobial chemotherapy. Of particular interest are bioreductive prodrugs such as nitro compounds or quinones that can initiate cytotoxic redox cascades and release active metabolites. The critical points for the selectivity of such molecules are, what is the source of the electrons that activate the prodrug, and which are the enzymes that catalyze the reduction? Meredith et al . conceive an elegant approach to answer these questions, making use of reverse genetics in Trypanosoma brucei . By overexpression of key reductase genes, they engineer trypanosomal indicator lines that are hypersensitive to particular bioreductive prodrugs and allow to discriminate between one‐electron and two‐electron transfer activation mechanisms. Indicator lines that are also defective in DNA repair further indicate whether the resultant metabolites interfere with the parasite's genome. This set of T. brucei indicator lines provides a tool for the deconvolution of the mechanisms of prodrug activation and drug action that will facilitate the rational development of bioreductive prodrugs for parasite chemotherapy.